Bile Acid Signaling in Liver Metabolism and Diseases. (3rd October 2011) - Li, Tiangang; Chiang, John Y. L.
Abstract : Obesity, diabetes, and metabolic syndromes are increasingly recognized as health concerns worldwide. Overnutrition and insulin resistance are the major causes of diabetic hyperglycemia and hyperlipidemia in humans. Studies in the past decade provide evidence that bile acids are not just biological detergents facilitating gut nutrient absorption, but also important metabolic regulators of glucose and lipid homeostasis. Pharmacological alteration of bile acid metabolism or bile acid signaling pathways such as using bile acid receptor agonists or bile acid binding resins may be a promising therapeutic strategy for the treatment of obesity and diabetes. On the other hand, bile acid signaling is complex, and the molecular mechanisms mediating the bile acid effects are still not completely understood. This paper will summarize recent advances in our understanding of bile acid signaling in regulation of glucose and lipid metabolism, and the potentials of developing novel therapeutic strategies that target bile acid metabolism for the treatment of metabolic disorders.